Comparison in tensile behaviour of conventional and high-strength steel welded-plate preloaded T-stubs. (September 2022) - Lin, Tao; Wang, Zhan; Hu, Fangxin; Hou, Weijie
Abstract: High-strength steels have been attracting more and more attention for engineering application due to their advantage in strength, but they are inferior in material ductility than conventional structural steels. In this paper the tensile behaviour of Q690 high-strength steel T-stubs connected by preloaded high-strength bolts was investigated by comparative experimental and numerical studies with those made of conventional structural steels. The test results revealed that the high-strength steel T-stubs provided about 12% higher ultimate resistance than conventional steel T-stubs of the same flange thickness and preloaded bolt type, but 18–41% lower ultimate deformation capacity on the basis of similar ultimate resistance. The β or β u factor based on the plastic or ultimate resistance of the T-stub components, respectively, might not capture accurately the actual failure modes. The limit in Eurocode 3 on the maximum flange thickness could be relaxed to be 20% higher for the high-strength steel T-stubs to obtain a better overall deformation capacity by exploiting the bolt-flange deformation balance, but the deformation capacity was also affected by bolt stripping, which needs further clarification. Finite-element analysis results evidenced that the design formulae in Eurocode 3 could be still applied to high-strength steel T-stubs in terms of the initial stiffness and plastic resistance, as well as the joint modelling approach. Jaspart and Maquoi's formulae are recommended over the design formulae in Eurocode 3 to calculate the plastic resistance of preloaded T-stubs, regardless of the steel grades.